PECULIARITIES OF VOCABULARY CONSTRUCTION IN THE ASSOCIATIVE-METAPHORIC DICTIONARY OF THE RUSSIAN LANGUAGE DESIGNED FOR THE NEEDS OF AUTOMATED TEXT PROCESSING SYSTEMS (AMD-ATPS) - Nikolai Golovko (Гуманитарные и юридические исследования)
The article presents an analysis of the head words parameters of a special associative-metaphoric dictionary designed to meet the actual needs of analytical algorithms of automated text processing systems, and on the basis of this analysis criteria for selecting lexical units into its vocabulary are formulated. A formal criterion is proposed, that reflects the spe-ciic features of metaphorical transition by means of external parameters of lexical units while taking into account the problematic nature of establishment of strict requirements for the selected words, conditioned by the essence of metaphor as the transfer of meaning by similarity. Also, a content criterion relying on selection of lexical units through their ability to constitute a basis for metaphorical transition, as well as through the principle of semantic basicity, understood as possibility of using a word to describe the semantics of as many other lexical units as possible, is proposed. Taking into account both criteria, a conclusion on advisability of using the existing experience in compiling active lexicographic databases and, in particular, the Prospectus for the Active Dictionary of the Russian Language (Moscow, 2010) as the basis for the vocabulary, is drawn, and also a construction procedure for this vocabulary is described.